Management consulting business models a perspective of sustainability - Pereira, L.; Jerónimo, C.; Ramos, M. R. (23rd International Conference on Engineering, Technology and Innovation, ICE/ITMC 2017, 2017)
In a world characterised by distorted information, Management Consulting is one of the fastest growing activities that has been questioned since its first appearance. Doubts have been floating around the limits of the industry, the role and utility of its practitioners and the consequent implicit value-added to the clients’ firms. As such the main objective of this research is to investigate the business models of consulting companies to understand the way they operate and how they contribute to attain a sustainable competitive advantage in the industries where they are present. This investigation was done by conducting interviews in 2015 and collecting personal testimonies through from top consultants of eight consulting firms. The findings suggest that all organisations that participated in the research possess a unique combination of interrelated mechanisms and approaches towards organisational structure, clients, consultants and projects, which indicates their concern to maintain and augment a sustained superior performance.